Triggering Immune System With Nanomaterials for Cancer Immunotherapy - Li, Qiyan; Liu, Yulin; Huang, Zihua; Guo, Yajie; Li, Qingjiao (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer is a major cause of incidence rate and mortality worldwide. In recent years, cancer immunotherapy has made great progress in the preclinical and clinical treatment of advanced malignant tumors. However, cancer patients will have transient cancer suppression reaction and serious immune related adverse reactions when receiving immunotherapy. In recent years, nanoparticle-based immunotherapy, which can accurately deliver immunogens, activate antigen presenting cells (APCs) and effector cells, provides a new insight to solve the above problems. In this review, we discuss the research progress of nanomaterials in immunotherapy including nanoparticle-based delivery systems, nanoparticle-based photothermal and photodynamic immunotherapy, and nanovaccines, nanoparticle-based T cell cancer immunotherapy and nanoparticle-based bacteria cancer immunotherapy. We also put forward the current challenges and prospects of immunomodulatory therapy.